STRATEGI PEMBERDAYAAN MASYARAKAT SEKITAR HUTAN KONSERVASI TAMAN WISATA ALAM GUNUNG BAUNG DALAM UPAYA MENGURANGI PERAMBAHAN HUTAN - Warsono Warsono; Soetriono Soetriono; Jani Januar (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
Mount Baung Natural Park is one of the conservation areas in East Java, to reduce encroachment by the public, the government holds community empowerment. This study aims to determine: the motivation of people in the area of empowerment; Socio-economic factors that affect the motivation of people in the areas in implementing empowerment programs; Strategies undertaken to empower communities in the areas. The research method uses a descriptive and analytic. Descriptive data analysis tools uses Likert scale, multiple linear regression and analysis of FFA. The results shows that the motivation of people on community development programsis high while the motivation of people on elephant grass in the Mount Baung Natural Park is low, socio-economic factors that influence on the motivation of people in the areas in implementing empowerment programs are age (years) , revenue (Rp), and the number of dependents (soul). While the factors that do not affect significantly are the education (years) and land area (m2). Strategies that can be done is: rehabilitate some areas of Mount Baung Natural Park that has been already degraded with labor-intensive methods and design tour packages which are capable of absorbing the local community as labor (tour guide) for tourists and researchers. Keywords :Community Empowerment, Forest Conservation, Encroachment.